The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1038/sj.bjp.0701296
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of α2‐adrenoceptors mediating contraction of dog saphenous vein: identity with the human α2A subtype

Abstract: 1 In the dog saphenous vein a 1 -and a 2 -adrenoceptors mediate noradrenaline-induced contractions in vitro. In order to study the a 2 -adrenoceptor in isolation, a 1 -adrenoceptors were inactivated by treatment of tissues with the alkylating agent phenoxybenzamine (3.0 mM for 30 min) in the presence of rauwolscine (1 mM) to protect a 2 -adrenoceptors. 2 Noradrenaline-induced contractions of tissues treated with phenoxybenzamine were antagonized competitively by the selective a 2 -adrenoceptor antagonist rauwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
2
39
1
1
Order By: Relevance
“…This profile is quite similar to those previously reported for tissues presenting mixed populations of a 1 -and a 2 -adrenoceptors and could indicate that clonidine might induce contraction of distal cauda epididymis by activation of both adrenoceptors (MacLennan et al, 1997;Dantas da Silva Junior et al, 2014). The consecutive contractions of distal cauda epididymis induced by clonidine led to diminished responses (desensitization, as previously defined by Neubig et al, 2003) as reflected by the decreased values of pD 2 and E max with repeated exposures.…”
Section: (A) (B) (C)supporting
confidence: 75%
“…This profile is quite similar to those previously reported for tissues presenting mixed populations of a 1 -and a 2 -adrenoceptors and could indicate that clonidine might induce contraction of distal cauda epididymis by activation of both adrenoceptors (MacLennan et al, 1997;Dantas da Silva Junior et al, 2014). The consecutive contractions of distal cauda epididymis induced by clonidine led to diminished responses (desensitization, as previously defined by Neubig et al, 2003) as reflected by the decreased values of pD 2 and E max with repeated exposures.…”
Section: (A) (B) (C)supporting
confidence: 75%
“…α 2 receptors are divided into several subtypes: α 2A , α 2B , α 2C . Pharmacological, autoradiographical and gene knock-out studies have shown that the α 2A subtype (Trendelenburg et al 1993;Van Liefde et al 1993;O'Rourke et al 1994) is the key α 2 receptor involved in the modulation of nociception Tracey et al 1995;Hunter et al 1997;Millan 1997Millan , 1998, cardiovascular function (MacLennan et al 1997), lipid metabolism (Tarkovács et al 1994), the release of noradrenaline, dopamine and serotonin (5-HT; Trendelenburg et al 1994;Millan et al 1994;Gobert et al 1997aGobert et al , 1998, and, probably, in mood states (Dickinson 1991). In the central nervous system, α 2A adrenoceptors are more widely distributed than α 2B and α 2C adrenoceptors, being detected in cortex, septum, dorsal horn and the endopiriform nucleus (Uhlén and Wikberg 1997).…”
mentioning
confidence: 99%
“…In the porcine palmer lateral vein and common digital artery, the low potency of prazosin suggests the presence of α 2A -adrenoceptors [12], and α 2A -adrenoceptors have also been reported in dog saphenous vein [86]. In the pig ciliary artery, the high potency of BRL44408 suggests the involvement of α 2A -adrenoceptors in contractions [143].…”
Section: α 2 -Adrenoceptors In Isolated Tissuesmentioning
confidence: 96%